Construção de um medidor de vazão tipo venturi: calibração e operação - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Using relatively easy-to-acquire devices, in addition to low cost materials, the present work focuses on the construction, evaluation and operation stages of a venturi flowmeter. Using research methods based on survey and bibliographical analysis, we will seek the necessary knowledge about the use of calibration and evaluation techniques found easily in the literature concerning the subject, and it is perfectly possible to construct a device similar to idealized by its creator, Giovanni Battista Venturi. Thus, the device constructed in this monograph refers to the classic Venturi Tube model, which is based on the calculations and methods that derive from the Bernoulli equation. After the construction, the device was started so that the equilibrium regime was reached. Thereafter, the process of flow regulation was initiated, using the manometer reading according to different amounts of fluids in the device. Although of handcrafted construction, the device presented good response to the calibration methods presented in the literature, as well as demonstrated quite accurately in its results, perfectly fulfilling its objective. Besides the confection, calibration and use of the device, the ease of use proves the reasons why the tool is the most used according to its primary purpose of measuring fluid flow.
Keywords: Tubo de Venturi; Vazão; Medição; Fluidos; Construção; CNPQ:: ENGENHARIAS